(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Due to migration of agricultural labor in non-farm sectors and increasing climate vulnerability it is a great challenge to keep pace of food production for the exponential growth of population in Bangladesh. For following the traditional paddy harvesting methods, significant amount of field losses has been occurred in every year. The study was conducted to evaluate performance of combine harvester in comparison to manual harvesting of paddy and identify the impact on agricultural production system in Bangladesh. The experiment was conducted at Wazirpur Upazila of Barisal district during Aman-2018 paddy harvesting using a combine harvester and also, manual harvesting was conducted at the same location. Financial analysis of combine harvester over manual method was carried out for comparison. Cost savings in mechanical harvesting of paddy were found 57.61% for using combine harvester over manual harvesting. Similarly, labors savings for using combine harvester was found 70% over manual harvesting. The estimated BCR of combine harvester is found 1.55. The break-even use of combine harvester is 35 ha/yr which indicates a combine harvester must operate above 35 ha/yr to have profit. The combine harvester will run on fully profit basis if it could be used after that minimum hectares. The average total harvesting losses (including harvesting, threshing and cleaning) were also found 1.61% and 6.08% for using combine harvester and manual harvesting, respectively. The losses of paddy will be reduced 4.47% using combine harvester over manual harvesting. The above results revealed that manual harvesting is a labor and cost involving system. On the other hand, mechanical harvester like combine harvester is a time, labor and cost saving system along with reducing harvesting losses. As a result, total paddy production might be increased, and which will help to contribute significantly to the development of livelihood status of rural community of Bangladesh. J Bangladesh Agril Univ 17(4): 583–591, 2019